Evaluation of gradation variation of the granite aggregates used in asphalt mixtures at their manufacturing place - Makulavičius, Mantas; Sivilevičius, Henrikas (International Conference “Environmental Engineering”, 2020)
Asphalt mixture gradation homogeneity is one of the key factors for proper laying and compaction during road pavement and its long-term maintenance afterwards. To achieve the good quality asphalt mixture homogeneity of aggregates used in road pavement must be kept in mind. Regarding to this, gradation variation of five different granite aggregates fractions (0/2, 2/5, 5/8, 8/11 and 11/16) from one of the largest manufacturing plants in Lithuania were determined in this paper. Total of 244 samples were taken from conveyer belt at the manufacturing place and all the data was evaluated by statistical methods providing histograms with theoretical curves of normal distribution. After that, the results were compared to each other and the requirements issued by Lithuanian road administration authority. Regression analysis was used to determine the dependence of standard deviation of percent passing and the mean percent passing through the sieves. The obtained research findings revealed that the maximum value of standard deviation of this dependence was equal to mean of 50% percent passing. Further investigations should include other aggregates quality parameters variation and its homogeneity throughout different stages of technological and transportation processes.
Keywords: aggregates; homogeneity; granite; gradation; variation; conveyor belt; fractions; mineral materials; standard deviation